(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
The main objective of the study was to test the performance and feasibility of SWAT model for prediction of stream flow in state of Jammu and Kashmir in India. The model was auto calibrated for a period of 8 years (2013 – 2021) using Swat Cup software. The SuFi2 algorithm in Swat Cup was adopted for auto calibration of the model. The calibrated model was validated for the three gauging stations for a period of 8 years (2013 – 2021). The land use map used for the calibration period was for the year 2013 and that for the validation period was for the year 2013. The simulated monthly stream low has Nash Sutcliffe efficiency value of 0.60, 0.69 and 0.71 for the calibration period for the said area respectively. The model results in good performance showing that it is feasible for predicting stream flow in under changing land use and climate conditions.